The Effect Of Anxiety, Information Technology Capability, and Trust On Employee Performance With Intension To Leave As An Intervening Variable At PT BPR Bank Jombang Perseroda - Asbari Nurpatria Kristin; Siti Mujanah; Sumiati Sumiati (Global Economics: International Journal of Economic, Social and Development Sciences, 2025)
PT BPR Bank Jombang Perseroda has developed well, and the increase in assets each year is significant, but the problems that still arise in the organization are high employee anxiety, due to the rapid development of information technology (increasingly sophisticated), and the level of trust is still relatively low and Intention to Leave is still not good, becoming a phenomenon in this study. The purpose of this study is to determine the effect of anxiety, IT Capability and trust on employee performance with Intention to Leave as an Intervening variable at PT BPR Bank Jombang Perseroda. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The population of the study were employees of PT BPR Bank Jombang Perseroda. The selection of respondents was carried out using the saturated non-probability sampling method with a total of 90 respondents. The data analysis method used descriptive analysis and SEM-PLS analysis. The results showed that the variables anxiety, IT Capability and trust had a positive and significant effect on employee performance through Intention to Leave of PT BPR Bank Jombang Perseroda employees.